1961
DOI: 10.1113/jphysiol.1961.sp006793
|View full text |Cite
|
Sign up to set email alerts
|

Studies of leptomeningeal collateral circulation in Macacus rhesus

Abstract: In previous experiments on dogs (Symon, 1960), it was shown that, within a few minutes of occlusion of a major cerebral vessel, free flow of blood occurred within the area of supply of the occluded vessel, borne via leptomeningeal anastomoses from the vascular fields of adjacent vessels. Since it has been established anatomically (Vander Eecken, 1959) that the number and size of collateral vessels within the pial circulation decreases with increasing convolution of the cortex in higher animals, it became of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

1967
1967
1988
1988

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 12 publications
1
14
1
Order By: Relevance
“…These anastomoses have been demonstrated anatomically many times (Heubner, 1872;Beevor, 1907 ;Vander Eecken & Adams, 1953) and function within a few moments of vascular occlusion in both the dog and macaque (Symon, 1960(Symon, , 1961. In the present experiments, both species showed an immediate fall in arterial pressure within the middle cerebral field on middle cerebral occlusion to similar levels, between 18 and 30 mm Hg, but in dogs there was frequently an elevation of this pressure within 2 or 3 min, and several dogs showed a restoration of pulse distal to the occlusion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These anastomoses have been demonstrated anatomically many times (Heubner, 1872;Beevor, 1907 ;Vander Eecken & Adams, 1953) and function within a few moments of vascular occlusion in both the dog and macaque (Symon, 1960(Symon, , 1961. In the present experiments, both species showed an immediate fall in arterial pressure within the middle cerebral field on middle cerebral occlusion to similar levels, between 18 and 30 mm Hg, but in dogs there was frequently an elevation of this pressure within 2 or 3 min, and several dogs showed a restoration of pulse distal to the occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…In the monkeys, anaesthesia was induced with thiopentone 20 mg/kg and maintained with chloralose 60 mg/kg. Previous experience (Symon, 1961) has shown that prolonged thiopentone anaesthesia in the monkey is unsatisfactory.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The variability of the clinical deficit produced by middle cerebral occlusion is well recognized, and it is probable that the two factors most involved in this variability are the variation in collateral potential from animal to animal -a relatively minor factor -and, more important, the variation from one experimental model to another in the degree of involvement of the perforating branches, 7 occlusion of which produces a dense ischemic lesion in the basal ganglia and internal capsule. Perfusion studies have demonstrated that the area of ischemia produced by middle cerebral occlusion in the monkey 8 or dog 9 is quite similar to that produced by acute middle cerebral obstruction, thrombosis, or embolization in man. The areas most densely involved are the Sylvian opercula and, provided the perforating arteries have been occluded by insult, the putamen and lentiform nucleus in the basal ganglia.…”
mentioning
confidence: 99%